2009
DOI: 10.3174/ajnr.a1633
|View full text |Cite
|
Sign up to set email alerts
|

Difficult Aneurysms for Endovascular Treatment: Overwide or Undertall?

Abstract: BACKGROUND AND PURPOSE:Aneurysm geometry has been shown to predict the need for adjunctive techniques in the endovascular treatment of intracranial aneurysms. We conducted a systematic retrospective study examining which thresholds of dome-to-neck ratio, maximum neck width, and aspect ratio of intracranial aneurysms best predict the need for adjunctive techniques in endovascular management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
78
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(83 citation statements)
references
References 10 publications
3
78
1
1
Order By: Relevance
“…6,[9][10][11][12] This analysis on the HELPS control arm confirms these as risk factors for recurrence. Aneurysms with a small D/N are prone to have neck remnants after coiling, which can result in recanalization of the aneurysm, because they are exposed to high wall shear stress and blood-flow velocities.…”
Section: Discussionsupporting
confidence: 51%
“…6,[9][10][11][12] This analysis on the HELPS control arm confirms these as risk factors for recurrence. Aneurysms with a small D/N are prone to have neck remnants after coiling, which can result in recanalization of the aneurysm, because they are exposed to high wall shear stress and blood-flow velocities.…”
Section: Discussionsupporting
confidence: 51%
“…26 Endovascular treatment of wide-neck or "difficult" aneurysms requires special techniques such as balloon-or stent-assisted coiling. 21 Because we did not document the decisions of our interventionists and neurosurgeons, we do not know to what extent the information provided by BSCTA has influenced patient management. We can state, however, that BSCTA assessed the site and shape of cerebral aneurysms as accurately as DSA.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 The most common and well-studied geometric determinant of treatment decisions and outcome is the dome-to-neck ratio. 21 Aspects of aneurysm geometry such as shape, size, dome-to-neck ratio, and location and the relationship to the parent vessels all may impact treatment decisions. 31,32 Interobserver agreement in our study was somewhat higher than that reported previously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aspect ratio (height to neck ratio) was measured. Furthermore, since aneurysms with maximum diameter º3 mm and aspect ratio º1.2 have morphologically been considered difficult to embolize, 1,2) and neck size AE4 mm indicates a``wide neck'' aneurysm, aneurysm diameters were dichotomized into º3 mm and AE3 mm groups, aneurysm neck sizes into º4 mm and AE4 mm groups, and aspect ratios into º1.2 and AE1.2 groups. Fisher's exact test was applied to compare these dichotomized variables between endovascular Endovascular Coiling for Ruptured Pericallosal Artery Aneurysms coiling success and failure cases.…”
Section: Methodsmentioning
confidence: 99%